2022
DOI: 10.3390/jcm11226623
|View full text |Cite
|
Sign up to set email alerts
|

LABA/LAMA as First-Line Therapy for COPD: A Summary of the Evidence and Guideline Recommendations

Abstract: Inhaled bronchodilators (alone or in combination) are the cornerstone of treatment for symptomatic patients with COPD, either as initial/first-line treatment or for second-line treatment escalation in patients who experience persistent symptoms or exacerbations on monotherapy. The Global Initiative for Chronic Obstructive Lung Disease 2022 report recommends initial pharmacological treatment with a long-acting muscarinic antagonist (LAMA) or a long-acting β2-agonist (LABA) as monotherapy for most patients, or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Bronchodilators are among the main measures to control symptoms in AECOPD [22]. The use of bronchodilators can improve respiratory symptoms, reduce the risk of deterioration, increase exercise tolerance, and improve quality of life in patients [23]. Our study indicated that the non-use of bronchodilators after admission was a risk factor for the occurrence of RF in AECOPD patients.…”
Section: Discussionmentioning
confidence: 59%
“…Bronchodilators are among the main measures to control symptoms in AECOPD [22]. The use of bronchodilators can improve respiratory symptoms, reduce the risk of deterioration, increase exercise tolerance, and improve quality of life in patients [23]. Our study indicated that the non-use of bronchodilators after admission was a risk factor for the occurrence of RF in AECOPD patients.…”
Section: Discussionmentioning
confidence: 59%
“…11,12 Largely, the recommendations are aligned between GOLD, ATS, Germany, Spain, and Japan, as well as between guidelines from many other countries or regions. 1,7,9,11,[13][14][15][16][17] For example, the ATS practical guidelines strongly recommend that any patient with dyspnoea and exercise intolerance should be given LABA/LAMA as first-line therapy. 10 It is important to acknowledge that guideline recommendations always refer to classes of drugs rather than specific LAMA, LABA, or ICS molecules (and their combinations) within each class.…”
Section: Recommendations In Guidelines: How Should Patients Be Treated?mentioning
confidence: 99%
“…Largely, the recommendations are aligned between GOLD, ATS, Germany, Spain, and Japan, as well as between guidelines from many other countries or regions. 1,7,9,11,1317 For example, the ATS practical guidelines strongly recommend that any patient with dyspnoea and exercise intolerance should be given LABA/LAMA as first-line therapy. 10…”
Section: Recommendations In Guidelines: How Should Patients Be Treated?mentioning
confidence: 99%
“…1 Bronchodilator therapy with long-acting muscarinic antagonist (LAMA) and/or long-acting β2-agonist (LABA) is the recommended initial treatment regimen for COPD management. 1 , 2 However, for certain patients with COPD who are at a higher risk of exacerbation while on dual bronchodilator therapy, triple therapy with an inhaled corticosteroid (ICS), LAMA, and LABA is recommended by the Global Initiative for Chronic Obstructive Lung Disease (GOLD). 1 Similarly, the Spanish chronic obstructive pulmonary disease guidelines (GesEPOC) 2021 recommend using triple therapy in high-risk patients whose exacerbations are not controlled with dual bronchodilator or ICS/LABA combination and with blood eosinophils ≥100 cells/µL.…”
Section: Introductionmentioning
confidence: 99%